2023
DOI: 10.1002/jsfa.12606
|View full text |Cite
|
Sign up to set email alerts
|

Sensory characterization of the perceived quality of East African highland cooking bananas (matooke)

Abstract: BACKGROUNDIt has recently become increasingly evident that banana projects in Uganda need to consider consumer preferences as part of the breeding process to increase the acceptability of new cultivars. A trained panel used quantitative descriptive analysis (QDA) as a tool to assess the sensory characteristics of 32 cooking bananas (matooke). The aim was to investigate which sensory characteristics best describe matooke.RESULTSFourteen descriptors were generated. The preferred attributes of matooke were high‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The colour of all the landrace genotypes were scored 7.4 and above, suggesting that the preference for intensity of yellowness in the matooke was high (towards a maximum of 10). 17 These descriptive scores coincided with genotypes with highly acceptable quality characteristics. 4,18 Landraces Kibuzi, Mbwazirume, Nakitembe and Mpologoma, all of them highly liked by users, were < 3.0, suggesting that users favor a soft texture (Table 2).…”
Section: Descriptive Sensory Analysis Of Textural Colour and Astringe...mentioning
confidence: 67%
See 3 more Smart Citations
“…The colour of all the landrace genotypes were scored 7.4 and above, suggesting that the preference for intensity of yellowness in the matooke was high (towards a maximum of 10). 17 These descriptive scores coincided with genotypes with highly acceptable quality characteristics. 4,18 Landraces Kibuzi, Mbwazirume, Nakitembe and Mpologoma, all of them highly liked by users, were < 3.0, suggesting that users favor a soft texture (Table 2).…”
Section: Descriptive Sensory Analysis Of Textural Colour and Astringe...mentioning
confidence: 67%
“…Previous studies identified the user-preferred physical and sensory quality characteristics of EAHCB and their descriptors. 4,17,18 In the present study, the bunch, finger, colour and textural qualitative user-preferred characteristics were translated into quantitative metric measurements to aid high-throughput screening of a large number of genotypes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Principal component analysis (PCA) linking qualitative and quantitative data PCA was used to determine the mean values of different characteristics and describe their relationships with the matooke samples. 40 PCA was used to summarize the relationships between CATA sensory characteristics, product samples and mean overall liking of each product scored by all the consumers, as well as for linking qualitative and quantitative data.…”
Section: Cata Testsmentioning
confidence: 99%